Expert System For Identifying Learning Style Types Using Forward Chaining Method At Corien Centre - Wibowo, Hafizh Fakhry; Maryaningsih, Maryaningsih; Lianda , Deri (Jurnal Komputer Indonesia, 2025)
Corien Centre is an institution engaged in human resource development, self-development, psychology, outbound and family gatherings, counseling, private lessons, and counseling processes at Corien Centre still use a manual system or face-to-face meetings between patients and experts. The Forward Chaining method in identifying learning styles at Corien Centre can assist experts in conducting counseling, which is still manual or face-to-face, less efficient in managing client data, and does not yet use digital storage or databases. This research designed a web-based application using PHP and MySQL so that it can be easily accessed by experts and users. Functionality testing was conducted using the black-box method on six main components: registration, login, feature input, suggestion input, diagnosis process, and output. The test results showed that all modules worked as expected. This expert system has been proven to improve the efficiency of the learning style identification process, ensure data security and orderly data storage, and facilitate access to digital counseling services. With the support of the forward chaining method, this system provides personalized learning solutions that can help the Corien Center provide more effective counseling guidance.